Assessment of Upper Body Kinematic Using Multiple Inertial Measurement Units - Rahman, Md. Mahmudur; Gan, Kok Beng; Woon, You Huay; Abd Aziz, Noor Azah; Huong, Audrey; Sim, Kok Swee (2025)
The use of a universal goniometer or expensive laboratory kinematic analysis equipment has traditionally served as the gold standard to quantify human body joint angle or joint range of motion measurement. However, the measurement of these human body kinematic parameters is now possible using a tiny, inexpensive, and portable wearable inertial measurement unit (IMU). The primary objective of this research is to assess the feasibility and accuracy of upper body kinematic measurement using multiple IMUs. The analysis in this study has considered the elbow and wrist joint angles, and the 12 healthy participants performed the assigned wrist (flexion/extension) and elbow (flexion/extension) movements with both hands. Three IMUs were used to measure the motion, and each joint angle was also measured with an electrogoniometer (EG). The data obtained from the IMUs were used to determine the joint angle, and the mean absolute error (MAE), mean squared error (MSE), and root-mean-square errors (RMSEs) were computed in comparison to the EG readings to evaluate the performance. An average RMSEs of 2.35◦ and 2.30◦ for elbow and wrist, respectively, were found for joint motion among the 12 subjects for all tasks. The maximum RMSE for both elbow and wrist joint angles was less than 5◦ , except for one measurement. A graphical user interface (GUI) was also designed and developed to help clinicians and therapists to assess patient progress, provide feedback, and motivate patients. The outcomes of our study revealed that the IMU system could be used to assess the upper extremity joint angles during functional motions.